Influence of Steady Temperature Field with Spray Lubrication Engaging-in/out on Shipping Helical Gear Tooth Surface - Ji Ruguang; Chen Weifang; Li Miaomiao (Jixie chuandong)
The gearbox is widely used in ships,studying its gear temperature field to avoid gear scuffing failure has larger significance. The rising temperature field by friction on gear tooth surface are simulated through the in- depth analysis of spray lubrication process of shipping helical gear,then the computational fluid dynamics（ CFD） method of spray lubrication process is established. Three types of spray ways including spray lubrication through engaging- in direction,spray lubrication through engaging- out direction,and spray lubrication through both engaging- in and engaging- out directions are calculated,and heat transfer coefficient of oil / air on meshing tooth surface of helical gear are obtained under different spray ways. The influence of different spray ways on meshing surface are compared under the influence on temperature with different heat transfer coefficient. The results show that,for better cooling effect,the oil should be sprayed both in engaging- in and engaging- out directions. The velocity of oil in the two directions depending on the structure,working condition of helical gear,but a better cooling effect has been calculated with 15 m / s in engaging- in and 45 m / s in engaging- out in this model.